Health Care Systems Efficiency and Institutions - Joumard, Isabelle (OECD Economics Department Working Papers, 2010)
This paper presents a set of indicators to assess health care system performance. It also presents new comparative data on health care policies and institutions for OECD countries. This set of indicators allows the empirical characterisation of health care systems and the identification of groups of countries sharing similar health institutions. It also helps to uncover strengths and weaknesses of each country's health care system and assessing the scope for improving value-for-money. The empirical analysis suggests that there is room in all countries surveyed to improve the effectiveness of health care spending; there is no health care system that performs systematically better in delivering cost-effective health care - big-bang reforms are therefore not warranted; increasing the coherence of policy settings, by adopting best policy practices within a similar system and borrowing the most appropriate elements from other systems will likely be more practical and effective to raise health care spending efficiency